The association of sugar-added food and beverages consumption with socioeconomic status and nutritional status among kemas preschool children in Kota Bharu, Kelantan - Munusamy, Hemala (Universiti Sains Malaysia, 2016)
High consumption of sugar-added food or beverages which is low in nutrient and high in calorie lead to an adverse effect on children general health. The objective of this study is to assess the association between the family socioeconomic status (SES) and nutritional status with frequency of sugar-added foods and beverages consumption of preschool children from Jabatan Kemajuan Masyarakat (KEMAS) in Kota Bharu District, Kelantan. This was a cross-sectional study of 219 participants from about 15 T ABIKA (KEMAS) in Kota Bharu, Kelantan. Anthropometric measurement were performed on the children and socioeconomic and Sugary Food Frequency Questioner (FFQ) was answered by their parents. The socioeconomic profile of the family shows their mean monthly household income permonth is RM1900 and their monthly household expenses for food is RM660 permonth. Most of the parent have highest education of secondary school, most of the mothers are not working (69.5%) but 2/3 of fathers working (85.4%) with average family size of 5 people or more ( 69. 4% ). According to the food frequency score the consumption of all the food item in FFQ were moderate or low. Five most common sugar-added food and beverages were consumed daily are chocolate drink (score 75.7), ice cream (score 58.0), "sirap" drink (score 51.3), sweets (score 49.3) and donut (score 49.0). For the assessment for BMI-for-age shows there was 8.7% and 20.5% of them were severe thinness and thinness respectively and 2.3%, 3.2% and 2.7% of them were in risk of overweight, overweight and obese respectively. For height-for-age, 1 .4% children were severely stunted and 9.6% were stunted while for weight-for-age shows, 9.1 % were severely underweight and 21. 0% were underweight. There were only several food items were associated with socioeconomic variable and also nutritional status of the children. Monthly household income had association with Cake (sponge cake (x2= 6.259; p value= 0.012) and normal cake (x2= 6.009; p value= 0.014)), "kuih" ("kuih lapis (x2= 5.316; p value= 0.021), "kuih akok" (x2= 6.262; p value= 0.012), "jala mas" (x2= 4.750; p value= 0.029), and "tahi itik" (x2= 4.743; p value= 0.029)), soya drink (x2= 5.174; p value= 0.023), "bubur kacang hijau" (x2= 6.103; p value= 0.013), "pengat pisang" (x2= 5.688; p value= 0.017) and ice cream (x2= 4.436; p value= 0.035). There were association between mother's education and consumption of"cokelat" (sweets) (x2= 6.447; p value= 0.011), wafer (x2= 4.918; p value= 0.027), com flakes (x2= 4.012; p value= 0.045), grape cordial drink (x2= 5.327; p value= 0.021), "sirap" drink (x2= 6.090; p value= 0.014), cordial drink (x2= 6.623; p value= 0.010), carbonated drink (x2= 4.919; p value= 0.027) and honey (x2= 4.644; p value= 0.031). For fathers education was only associated with consumption of wafer (x2= 7.888; p value= 0.005) and com flakes (x2= 4.943; p value= 0.026). Mother's occupation had association with consumption of chocolate chip and milk biscuit (x2= 4.274; p value= 0.039) and donut (x2= 4.156; p value= 0.041) while fathers occupation was only had association with pineapple juice (x2= 12.662; p value, < 0.001). Household size had association with consumption of chocolate chips and milk biscuit (x2= 5.615; p value= 0.018). Monthly household expenditure for food had association with consumption of chocolate chips and milk biscuit (x2= 4.814; p value= 0.028) and "sirap" drink (x2= 4.434; p value= 0.035). The nutritional status (BMI-forage) show association with "kuih" (donut (x2= 7.738; p value= 0.021), "kuih kasui" (x2= 7.534; p value= 0.023), and "kuih seri muka" (x2= 8.238; p value= 0.016)) and "bubur kacang merah" (x2= 8.442; p value= 0.015). Height-for-age showed association with normal cake (x2= 4.578; p value= 0.032), "kuih seri muka" (x2= 4.332; p value= 0.037), "pulut panggang" (x2= 4.838; p value= 0.028), apple juice (x2= 6.934; p value= 0.008), grape juice (x2= 4.967; p value= 0.026), lemon juice {x2= 4.882; p value= 0.027), and "cole rojak" (x2= 3.866; p value= 0.049). The nutritional status (weight-for-age) showed significant association with plain biscuit (x2= 5.709; p value= 0.017) and "pulut panggang" (x2= 6.215; p value= 0.013). As a conclusion there is significant association between frequency of several type of sugar-added food and beverage consumed by children with the socioeconomic variable and nutritional status (BMI-for-age, height-forage and weight-for-age) of the children.